Regulation of neutrophil functions through inhibitory receptors: an emerging paradigm in health and disease. Issue 1 (September 2016) - Favier, Benoit
Summary: Neutrophils are the most abundant subset of leukocytes and play a crucial role in the immune responses against the daily pathogen attacks faced by the host. Neutrophils exhibit several functions for fighting microbes, including the release of granules containing highly toxic molecules, the production of reactive oxygen species and inflammatory cytokines as well as NETosis. Therefore, immune responses mediated by neutrophils must be tightly regulated to protect the host from pathogen assaults without inducing detrimental inflammation and tissue damage. There is now compelling evidence showing that neutrophils express various inhibitory receptors that specifically control their functions. Some of these inhibitory receptors are contained in the membrane of granules and rapidly move to the cell surface upon neutrophil stimulation. This fast upregulation of inhibitory receptors is an efficient way to rapidly enhance inhibitory signals and increase the neutrophil activation threshold. However, because of their ability to attenuate the immune responses of neutrophils, the inhibitory receptors are attractive target for pathogens. This review discusses these various aspects with a particular emphasis on the regulation of neutrophil behavior through immunoreceptor tyrosine‐based inhibition motif (ITIM)‐bearing inhibitory receptors belonging to LILR and SIGLEC multi‐gene families in humans and animal models.